Association Between Collision Sport Career Duration and Gait Performance in Male Collegiate Student-Athletes. Issue 9 (July 2022) - Oldham, Jessie R.; Lanois, Corey J.; Caccese, Jaclyn B.; Crenshaw, Jeremy R.; Knight, Christopher A.; Berkstresser, Brant; Wang, Francis; Howell, David R.; Meehan, William P.; Buckley, Thomas A.
Background: Investigations of estimated age of first exposure to repetitive head impacts from collision and contact sports have shown no associations with neurocognitive or neurobehavioral function at the collegiate level, but the effect of career duration may be a more comprehensive factor. Understanding whether longer career duration influences gait performance would provide insights into potential neurological impairment. Purpose: To examine the relationship between career duration of collision sports and single/dual-task gait performance in collegiate student-athletes. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We recruited 168 male student-athletes from collision sports: football, lacrosse, ice hockey, and wrestling (mean ± SD age, 19.2 ± 1.3 years; height, 184.5 ± 7.2 cm; mass, 94.3 ± 15.9 kg; estimated age of first exposure, 8.6 ± 3.1 years; career duration, 10.6 ± 3.0 years). All participants completed a baseline single- and dual-task gait assessment before the start of their athletic season. Inertial measurement units were used to measure gait speed and stride length. During the dual task, participants were asked to perform working memory cognitive tasks while walking. The dependent variables were single/dual-task gait speed and stride length, cognitive accuracy, and dual-task cost. The relationship between career duration, analyzed as a continuous variable, and the dependent variables was analyzed using a linear regression. Results: There were no significant associations between career duration and single-task gait speed (1.16± 0.16 m/s; β = −0.004; P = .35; 95% CI = −0.012 to 0.004; η 2 = 0.005) or dual-task gait speed (1.02± 0.17 m/s; β = −0.003; P = .57; 95% CI = −0.011 to 0.006; η 2 = 0.002). There were also no significant associations between career duration and single/dual-task stride length, cognitive accuracy, or dual-task cost. Conclusion: Career duration among collegiate collision sport athletes was not associated with single- or dual-task gait performance, suggesting that a greater exposure to repetitive head impacts is not detrimental to dynamic postural control at the college level. However, the effects of diminished gait performance over the lifetime remain to be elucidated.